Franz and the Algerian revolution(1954-1962) - Aissa, Litim Aissa; Belferdi , jamel (Humanities Journal of University of Zakho, 2020)
Despite the recurrent momentum of historical and intellectual studies and literature on the Algerian liberation revolution 1954-1962 as a founding event for the contemporary history of Algeria, especially the French writings, which drew a certain pattern of ideology that serves the purposes of the French colonial historical school in the first place, and perhaps the study in our hands is worthy to be a field It is a field for analysis, criticism, and comparison to go beyond the epic and ceremonial images that we find in the official readings of the topics in which politics intersect with historical legitimacy, and ideologies intersect with the civilizational principles of the Algerian revolution. And between this and that, the researcher finds himself when delving into the topics and issues related to the liberation revolution, including the subject of Frantz Fanon's contributions to this founding event of the contemporary Algerian state, in which numerous writings have attempted to present a coherent picture of this character of Martinique of origin, Algerian presence, and African influence and influence.The aim of this study is to shed light, analytically and critically, on the basic features of the contributions of this global intellectual stature to the issue of the ideological development of the Algerian revolution after 1958, and bypassing the trend of some historical and social studies that reach the point of denying the charters and reference texts of the Algerian revolution. Ahead of "the document of the first of November 1954, and the document of the Soumam conference 1956," and established a historical background according to which Fanon is a viewer of the Algerian revolution.